Effect of the number of pregnancy in the dental health status of mothers. (Mustansiria Dental Journal, 2005)
The aim of study was to evaluate the effect ofthe number of pregnancy inthe dental health of iraqi women .Three hundred ninety nine pregnant women were included in this study, withan age range of 18-39 years old. They were attending to the Maternal and ChildHealth Care Center (MCHCC) for their monthly periodic checkup with differentpregnancy stages. The sample of the study was randomly selected from four out of 16MCHCCs in the center of Mosul city .Caries experience were diagnosed and recorded according to the criteriasuggested by WHO 1997 using CPI probe. The (DMFS) index was used to assess thedecayed, missing and filled surfaces .The periodontal health status of pregnant women was performed using thefollowing clinical parameters (gingival index, plaque index and calculus index .)To evaluate the effective of number of pregnancy on dental health status, thesample divided into three group (1-3) according to the number of pregnancy (1-3, 4-6 ,)75 respectively .The result indicated an increase in the mean of DMF S score with an increasein the number of pregnancy; also the study indicates a significant increase in the meanof periodontal parameters with an increase in the number of pregnancy